Pengaruh Model Pembelajaran Inkuiri dengan Bantuan Media Tiga Dimensi Terhadap Keterampilan Proses Sains dan Hasil Belajar Fisika Peserta Didik - Ridayatul Jannah Putri Maharani; Muhammad Taufik; Syahrial Ayub; Joni Rokhmat (Jurnal Penelitian Pendidikan IPA, 2020)
This study aims to determine the effect of inquiry learning models with three-dimensional media on science process skills and physics learning outcomes of students. This study uses quasi-experiment by taking work and energy topics. Data collection on science process skills using an observation sheet. Whereas for the learning outcomes data is done with multiple choice test techniques as many as 25 questions. Data analysis using manova test with significant obtained at 0.00 (significant <0.05). With a significance of less than 0.05 this shows that there is influence on the experimental class and the control class on, so it can be concluded that the application of the inquiry learning model with the help of three-dimensional media has an influence on students' science process skills and physical learning outcomes.